Research on Earthquake Induced Liquefaction in Padang City and Yogyakarta Areas - Muntohar, Agus Setyo (Himpunan Ahli Teknik Tanah Indonesia (HATTI), 2014)
Awareness and research on earthquake resistant building design has been intensively carried out after the fatal earthquakes in Indonesia in recent decades. However, less attention has been given to the phenomena of liquefaction due to lack of ground motion information and records at the hazard areas. In this paper, seismic ground response after two deadly earthquakes shocked Java and Sumatera (Indonesia) in 2006 and 2009 was evaluated based on the CPT data. Based on back-calculation results, the possible ground accelerations were expected to be about 0.48g and 0.14g in those liquefied areas at Yogyakarta (Southern Java) and Padang (West Sumatera) respectively. Those accelerations are likely to make 50% of the thickness of sand layer liquefied and induced about 1% ground settlementKeywords : liquefaction, peak ground acceleration, silty sand, CPT